EVALUATION OF RISK FACTORS OF NON ALCOHOLIC FATTY LIVER DISEASE (NAFLD) IN A TERTIARY CARE HOSPITAL AT RAWALPINDI, PAKISTAN: A LOCAL EXPERIENCE - Bano, Uzma; Gondal, Murtaza; Moin, Shaheen (Journal of Postgraduate Medical Institute, 2011)
Objective: To document the frequency of risk factors for nonalcoholic fatty liver disease, such as gender, diabetes mellitus, hypercholestrolemia, hypertriglyceridemia, obesity and metabolic syndrome. Material and Methods: This descriptive study was carried out at Department of Medicine Fauji Foundation Hospital Rawalpindi from January 2007 to December 2007 One hundred nonalcoholic patients with elevated ALT and negative viral serology and diagnosed as having fatty liver on ultrasound were evaluated for the presence of diabetes, hypercholestrolemia, hypertriglyceridemia, obesity and metabolic syndrome. Patients with suspected autoimmune hepatitis, hemochromatosis and Wilsons disease were excluded. Results: The mean age was 45.39 years. Out of 100 patients, 63% were females and 37% were males. Sixty six percent patients were obese. Other risk factors included hypertriglyceridemia in 48%, diabetes mellitus in 34%, hypercholesterolemia in 28% and metabolic syndrome in 28% cases. Conclusion: Nonalcoholic fatty liver disease is associated with a high prevalence of obesity, hypertriglyceridemia, hypercholestrolemia, diabetes and female gender.